Exploring nurses' use of the WHO safety checklist in the perioperative setting. (18th October 2016) - O'Brien, Brid; Graham, Margaret M.; Kelly, Sile Mary
Abstract : Aim: To explore nurses' use of the World Health Organization safety checklist in the perioperative setting. Background: Promoting quality and safety in health care has received worldwide attention. The World Health Organization surgical safety checklist (2009) is promoted for reducing postoperative morbidity and mortality. The checklist has been introduced in Irish perioperative settings. Method(s): A descriptive, qualitative approach was utilised. A purposeful sample of ten nurses participated in individual, semi‐structured interviews. Results: Participants were committed to promoting safety in navigating challenges in introducing, complying and accepting the value of the World Health Organization surgical safety checklist in concordance with best practice. Participants moved from task completion to embracing the checklist as an effective surgical safety checking tool. Challenges were identified around roles and responsibilities in overseeing the completion of the checklist. Conclusion(s): The management of processes is critical when implementing any safety initiative. This paper highlights the complexity and challenges in implementing the World Health Organization surgical safety checklist, contributing to global discussions around translating policy into practice. Implications for nursing management: The effective implementation of a checklist requires a coordinated management approach in collaboration with team members. These approaches will support learning experiences contributing to a shared understanding of the change being implemented by all team members.